THE IMPLEMENTATION OF CLIL FOR YOUNG LEARNERS: A PRISMA SYSTEMATIC REVIEW - Sri Ananda Pertiwi; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2024)
The purpose of this study is to review the implementation of CLIL to young learners. The database Scopus was examined and 5 articles in all were examined for this purpose. The research methodology employed was a PRISMA systematic review. A content analysis technique was used to assess the articles. The study’s findings revealed that the trend of CLIL (Content and Language Integrated Learning) research for young learners is in elementary level, aged 5-12 years. The results indicated that CLIL impacts students' motivation and language competence, particularly in vocabulary enrichment, the receptive aspect rather than the productive aspect.